An examination of parental awareness and mediation of media consumed by fifth grade students - Springer, Dustin Michael (Kansas State University, 2011)
This dissertation investigated parental roles in mediating television, music, and the Internet for their children--specifically their fifth graders. Seventy two parents, representing forty seven fifth graders took part in the study. The Television Mediation Scale (Valkenburg, Kremar, Peeters, & Marseille, 1991) provided a framework for the instrument used. Parents were asked a series of questions dealing with television, music, and the Internet. Responses were given on a four point Likert scale. Additionally, participants were asked to estimate the amount of time spent with each medium, discuss the rules in place, the concerns they have with the media, and what principles guide their decisions about how their child uses each type of media. Regarding television, results indicated that parents utilized the restrictive mediation style in which parents set rules for viewing television programs or even prohibit certain shows from being seen. Although parents report using restrictive mediation, more than likely co-viewing is being used most frequently (Weaver & Barbour, 1992). This is plausible when applied to this study considering how close the Mean values are between restrictive mediation (3.36) and co-viewing (3.28). Statistically, no significant findings were reported in regards to music and Internet mediation. However, from a qualitative viewpoint, a wealth of data was gathered regarding the guiding principles and rules that are in place in each home regarding the media. Overall, parents report being knowledgeable of the media that their child uses and are comfortable with the rules in place and the principles that guide their decisions. The results of the study indicate that parents are aware of how their child/children interact with the media but an element of education for parents and even educators in the schools may be missing. Parents must stay abreast of new technologies and continually monitor ways in which their child/children use that technology. If parents believe that they are helpless against the power the media has over their children they are conceding a loss to the media's influence. However, if parents stay involved in their child's life and stay up-to-date on the newest technologies and what children gain from using this technology, then there is no reason to believe that we are powerless against the media.
Keywords: Media; Adolescence; Television; Music; Internet; Parents; Elementary; Education, Elementary (0524); Mass Communications (0708)